Allgrove syndrome and motor neuron disease - Marcos R.G. de Freitas; Marco Orsini; Alexandra Prufer de Queiroz Campos Araújo; Luiz João Abraão Jr; Gilberto Miranda Barbosa; Marcondes C. França; Luan Correia; Victor Hugo Bastos; Eduardo Trajano; Mauricio da Sant'Anna Jr (MDPI AG, 2018)
Allgrove or triple A syndrome (AS or AAA) is a rare autosomal recessive syndrome with variable phenotype due to mutations in AAAS gene which encodes a protein called ALADIN. Generally, it's characterized by of adrenal insufficiency in consequence of adrenocorticotropic hormone (ACTH) resistance, besides of achalasia, and alacrimia. Neurologic features are varied and have been the subject of several case reports and reviews. A few cases of Allgrove syndrome with motor neuron disease have been already described. A 25-year-old white man, at the age of four, presented slowly progressive distal amyotrophy and weakness, autonomic dysfunction, dysphagia and lack of tears. He suffered later of orthostatic hypotension and erectile dysfunction. He presented distal amytrophy in four limbs, tongue myofasiculations, alacrimia, hoarseness and dysphagia due to achalasia. The ENMG showed generalized denervation with normal conduction velocities. Genetic testing revealed 2 known pathogenic variants in the AAAS gene (c.938T>C and c.1144_1147delTCTG). Our case presented a distal spinal amyotrophy with slow evolution and symptoms and signs of AS with a mutation in AAAS gen. Some cases of motor neuron disease, as ours, may be due to AAS. Early diagnosis is extremely important for symptomatic treatment.